Analysis of Empirical Study on the Impact of Esg Risk Score and Dividend Payout Ratio on Issuer Valuation - Ramadhan, Bayu; Rosdini, Dini; Yuliafitri, Indri (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
This study investigates the influence of ESG Risk Score (ESGR) and Dividend Payout Ratio (DPR) on the valuation of companies listed on the Indonesia Stock Exchange (IDX) that have consistently received ESG Risk Ratings from 2019-2022 by Morningstar Sustainalytics. Sustainability Financial & ESG are being the main activities for development of the Sharia capital market and achieving the Sustainability Development Goals (SDGs). The research method is descriptive and verification research through purposive sampling of 53 companies that implemented early regulations related to Sustainable Finance. This study identifies ESGR and DPR as factors influencing valuation. The results show that neither ESGR nor DPR affect company valuation. The variable simultaneously test results indicate no collective impact on company valuation. The conclusion is that ESGR and DPR have not impacted valuation and shown that the implementation of ESG in Indonesia still on the early stages that have a lot potential for development (i.e literacy, information technology, infrastructure and regulations for implementation of ESG program).